EFEKTIVITAS MEDIA POWTOON TERHADAP HASIL BELAJAR X IPS MATA PELAJARAN SEJARAH MAN 2 PONTIANAK - Rista Anggraini; Ika Rahmatika Chalimi; Astrini Eka Putri (Universitas Tanjungpura, 2022)
This research aims to determine whether there is an effect of usedPowtoon-basedPower Point media learning. This research was conducted in MAN 2 Pontianak withstudents in class X IPS 1 and X IPS 2. The research method used in this research isdescriptive quantitative method. The data in this study were in the form of studentlearning outcomes and learning evaluation question sheets. Data analysis usedMicrosoft Excel 2010. This research produces some data such as the value of studentlearning outcomes before and after usedPowtoon learning media, validity test,reliability test, normality test, homogeneity test, hypothesis test, and Effect Size test.Student learning outcomes have increased after used the Powtoon learning media.Learning outcomes before used powtoon media in the control class were 55.3 whilefor the experiment class the averange learning outcomes were 63. Learning outcomesafter used powtoon media had increased, especially in the Ekperiment class. For theControl class in this Post-Test activity, the average student learning outcomes are58,2. While the average student learning outcoes in the Ekperiment class is 76,6. Testof the hypothesis it is known that t is 1.99, which means that the used of this media has an effected on the learning outcomes of students. The last one is the Effect Size test which scores 0.15 in the